The prevalence of Temporomandibular Disorder (TMD) and its severity among YARSI University Employees - Helwiah Umniyati (Journal of Dentomaxillofacial Science, 2020)
Objective:This study described the prevalence of Temporomandibular Disorder (TMD) and its severity among YARSI University employees.Material and Methods: It was a cross sectional analytical study based on Fonseca’s Questionnaire.Results: The sample consisted of 225 participants, 118 of them were men (52.4%) and 107 of them were women (47.6%), with an average age of 37.99 ± 12.05 years old. Almost all of the samples (92%) informed that they did not have a difficulty in mouth opening and moving the jaw to the sides (92%), 84% reported no clenching teeth and 80% reported no articulation disorders. While 34.8% of respondents reported muscular pain during mastication and 38.7% reported suffering from frequent headaches occasionally. Temporomandibular Joints (TMJ) clicking was reported among 13.3% of participants and only a very small number of samples (4.9%) reported pain in the temporomandibular joint.Conclusion: The prevalence of TMD was quite high i.e 50.7%. In term of severity, most of subjects had mild TMD’s (86.8%). The sociodemographic factors that significantly associated with severity of TMD were education and work status.